ANALISIS SOCIAL CAPITAL DALAM CAPAIAN PROGRAM PERENCANAAN PERSALINAN DAN PENCEGAHAN KOMPLIKASI (P4K) - SITI PATONAH, SITI PATONAH (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2012)
The number of death mother in Indonesia is still high, there fore it needs penetration to decrease AKI through Program Planning Safe Motherhood ang Prevention Komplication. Goal is program to cause to need the resource. Having a from resource nature or resource human. Resource in society stated capital. Either a from capital in society of  stated social capital. The aim of this research to analyze social capital in achieving P4K in Ngablak village, Ngumpak Dalem local clinic and Bungur village, kanor local clinic Bojonegoro.The research was done by Analyze. There were 66 families in Bungur village and 65 families in Ngablak village. The sample was taken by simple random sampling. The data was processed by quantitatif with analyzed by test Mann-Whitney . It was supported with qualitatif by indepth interview and FGD  with contents analyze.The result showed that Social Capital of Ngablak?s village society in belief paremeter trust was mostly in average, a norm also support separetely and the social networking was very supported. Social Capital of Bungur?s village society in belief paremeter trust was mostly high, a norm was mostly very support and the social networking  was also support highly.                The conclusion, there were significant differences Social Capital in achieving P4K in Ngablak village, Ngumpak Dalem local clinic and Bungur village, Kanor local clinic Bojonegoro. The recomendation are the society belief have to increase by communication  and interaction between society and village?s motivator. In supporting norm, it needs a model from village?s motivator and in increasing connection, it needs a good working beetween village motivator, village apparatus, society figure, religion figure in the organizatin activitiesKey words: Death mother, social capital, trust, norm, social networking, P4K